Anatomy of the Facial Nerve at the Condylar Area: Measurement Study and Clinical Implications. (14th October 2014) - Yang, Hun-Mu; Yoo, Young-Bok
Abstract : The aim of this study was to elucidate the detailed anatomy of the facial nerve (FN) at the condylar area to helping physicians preventing the iatrogenic trauma on the nerve. We dissected 25 specimens of the embalmed Korean cadavers (13 males and 2 females; mean age 76.9 years). The FN course at the condylar was examined, and the location of the FN branches was measured with superficial standards. The trunks of the FN emerged in the condylar area as one trunk, two trunks, and a loop or plexiform in 36%, 12%, and 52% areas, respectively. The zygomatic branch (Zbr) of FN passed over the tragus-alar line 23 mm anterior to the tragus (Tg) in most of the cases. The Zbr passed over the vertical line 2 cm anterior to the Tg through the area about 6 to 20 mm inferior to the Tg. Regardless of careful approach techniques to the condylar area, the FN could be damaged by a careless manipulation. Any reference landmarks could not guarantee the safety during the approach to the condylar area because more than half of the cases present the complicated branching type in the front of the Tg.